THE CULTURE OF READING AND THE AESTHETIC PERCEPTION OF LITERARY TEXTS (Modern education and development, 2025)
the culture of reading and the aesthetic perception of literary texts hold a significant place in the spiritual life of an individual, shaping their worldview and interaction with the surrounding world. This study examines the role of literary texts in understanding reality, preserving cultural heritage, and forming national identity. Practical recommendations are proposed to maintain the depth of literary perception, contributing to the development of empathy, critical thinking, and aesthetic taste.